Analysis of rice massive importing impact towards poverty alleviation in indonesia based on micro, macro, politics and international economics - Yusrin, Nur Amalyna; Nugroho, Arissetyanto; Darmansyah, Darmansyah (Proceeding International Conference on Accounting and Finance, 2024)
Rice is a highly significant staple food commodity globally. This statement is notably true on the Asian continent, where rice acts as the primary food for the majority of the population, particularly among the lower middle class. Asian farmers contribute for over 90% of global rice production. Indonesia is one the biggest rice producer in the world were contributing 53,63 million tonnes in 2023. However, the Indonesia government still need to import massively around 3 million tonnes of rice at the end of 2023 and still continuing in 2024. Comparing to the historical data, Indonesia has been rice self-sufficiency country in 1980s and nowadays is not reached due to some advanced economic issue. Previous research shows distinct results of rice importing impact, some stating that importing beneficial however some explained it is increasing number of pverty in Indonesia. This study will analyse the benefits and the disadvantages impact of rice importing massively in Indonesia towards Poverty Alleviation through literature study from macroeconomics, microeconomics, international economics and politics economics. The output is recommendation for managerial stakeholders to create the welfare for each stakeholder and the idea of creating the rice self-sufficiency vision.